The Effect Of Non-Product -Based Performance Criteria Towards Supplier Selection Process - Yeo, Cheang Sze (2005)
This study attempts to identify the effect of non-product-based performance criteria (qualitative factors of soft criteria) towards supplier selection process. Eight key non-product-based performance criteria discussed in the study are delivery, responsiveness, organization size, financial status, location of manufacturing plant, relationship history, certificates or quality system requirement and organization culture.